2017
DOI: 10.15406/ipmrj.2017.02.00041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesiotaping on Handgrip Isometric Strength in Athletes

Abstract: Purpose: To measure the acute effects of Kinesio Taping (KT) on handgrip maximal isometric strength (MIS) and strength endurance (SE) in healthy athletes.Methods: Experimental study with repeated measures and randomization. 37 healthy men, in which 19 play racquet sports and 18 were Brazilian jiu-jitsu (BJJ) athletes. The subjects were submitted to three distinct taping conditions for the variables measurement. i. No taping application (GSB)ii. KT Application (GKT)iii. Placebo Taping Application (GBP)The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The above findings were consistent with recent ob- servations that there were no major improvements in muscle strength efficiency following KT (15,20,21). In accordance with the results of this study, the Zanchet et al findings did not support the use of "I" shape KT on the ventral forearm in increasing muscle strength in healthy athletes (18). Zhang et al also showed the incapacity of forearm KT to reinforce hand grip strength immediately in healthy athletes (16).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The above findings were consistent with recent ob- servations that there were no major improvements in muscle strength efficiency following KT (15,20,21). In accordance with the results of this study, the Zanchet et al findings did not support the use of "I" shape KT on the ventral forearm in increasing muscle strength in healthy athletes (18). Zhang et al also showed the incapacity of forearm KT to reinforce hand grip strength immediately in healthy athletes (16).…”
Section: Discussionsupporting
confidence: 59%
“…The study was conducted as a quasi-experimental trial on thirty-three elite female squash players. The sample size calculation was made using the G*Power statistics software (v.3.1.2, Universität Kiel, Alemanha), considering the Zanchet et al (18) findings and assuming a power of 80%, effect size of 0.8 and α = 0.05, at least 30 athletes would be necessary to perform the study.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance muscle power, Kenzo Kase sug-gested taping with 25-35% tension [15]. However, other researchers recommended 50% tension, while Atrib Zanchet et al [16] demonstrated that KT with 25% tension did not demonstrate any changes in the handgrip strength.…”
Section: Introductionmentioning
confidence: 99%